Use of monoclonal antibodies in oncology - Enriquez-Vera, Daniel (2021)
Monoclonal antibodies represent a fundamental cornerstone in the management of cancer. These advanced biological compounds have achieved a significant improvement of survival in patients. Among the most renown antibodies: rituximab, bevacizumab, cetuximab, trastuzumab are the most used in our local daily practice. In the last decade, immunotherapy has been positioned as an efficacious therapy for adverse diseases such as melanoma, lung, and renal neoplasms. In the nearest future, new conjugated antibodies, and CAR-T therapy will represent models of innovative strategies to cure cancer.